Characterizing patients with high use of the primary and tertiary care systems: A retrospective cohort study. Issue 3 (March 2020) - Singer, Alexander; Kosowan, Leanne; Katz, Alan; Ronksley, Paul; McBrien, Kerry; Halas, Gayle; Williamson, Tyler
Highlights: Almost one-third of patients had high use of a health service at one point in time. Five percent of patients have persistent high use of a health service. Primary care utilization and hospital admissions are associated with medical complexity. Emergency service utilization and longer hospital stay are associated with social complexity. Abstract: Objectives: To utilize complementary data from primary care and administrative health and social services to describe the clinical, social and demographic characteristics of high users of health care services. Methods: We conducted a retrospective cohort study using data from the Manitoba Primary Care Research Network (MaPCReN) and the Manitoba Centre for Health Policy Research Data Repository in Canada. We assessed data from 193, 760 patients with at least one visit to a primary care provider between 2011 and 2016. We defined HU within the following areas: primary care, hospital discharges, length of stay and emergency department visits. Descriptive statistics and logistic regression was used to identify key demographic, social, and medical complexities associated with HU. Results: Between 2011 and 2016, 30.8 % of patients had HU during at least one year within at least one area. Among patients with HU, 5 % had persistent HU (HU for ≥2 years) and 359 (0.6 %) had HU across all four definitions. Medical complexity was associated with HU for patients with hospital discharges, ED visits and primary care visits, whereas socially complex patients were more likely to have a longer LOS, and visit the ED. Conclusions: There were unique characteristics in the various HU cohorts including medical, social, and demographic features that can inform strategies aimed at improving health system efficiency in managing patients with HU.